Implementation of a "threat and error" model in complex neonatal cardiac surgery patients to identify quality improvement opportunities. (1st June 2020) - Todd Tzanetos, Deanna R.; Montgomery, Vicki; Harrington, William; Calhoun, Aaron
Abstract: Introduction: Neonates undergoing surgery for congenital heart disease are vulnerable to adverse events. Conventional quality improvement processes centring on mortality and significant morbidity leave a gap in the identification of systematic processes that, though not directly linked to an error, may still contribute to adverse outcomes. Implementation of a multidisciplinary "flight path" process for surgical patients may be used to identify modifiable threats and errors and generate action items, which may lead to quality improvement. Methods: A retrospective review of our neonatal "flight path" initiative was performed. Within 72 hours of a cardiac surgery, a meeting of the multidisciplinary patient care team occurs. A "flight path" is generated, graphically illustrating the patient's hospital course. Threats, errors, or unintended consequences are identified. Action items are generated, and a working group is formed to address the items. A patient's flight path is updated weekly until discharge. The errors and action items are logged into a database, which is analysed quarterly to identify trends. Results: Thirty one patients underwent flight path review over a 1-year period; 22.5% (N = 7) of patients had an error-free "flight." Eleven action items were generated – four from identified errors and seven from identified threats. Nine action items were completed. Conclusions: Flight path reviews of congenital cardiac patients can be generated with few resources and aid in the detection of quality improvement opportunities. The regular multidisciplinary meetings that occur as a part of the flight path review process can promote inter-professional teamwork.